Keban Lewa Lolon: Inspirasi Lumbung Pangan untuk Kebijakan Pengelolaan Wilayah Pesisir di Indonesia - Tatu Sius, Karolus; Niron, Inosensia Nogo; Palan Peten, Yasinta Y.; Kaha, Hendrikus L.; Ratumakin, Paulus Adrianus K. L. (Nakhoda: Jurnal Ilmu Pemerintahan, 2024)
This study starts from the paradox of coastal and marine management. On the one hand, marine resources provide various potentials that bring various benefits from their ecosystem services. However, on the other hand, coastal and marine utilization often causes conflict due to mismanagement, ignoring community participation and excessive economic orientation without considering social and environmental aspects. This study uses qualitative methods to explore the meaning of keban in general and its functions. Coastal and marine management models in the form of conservation/protection, utilization, and ecosystem improvement can be carried out through two approaches. The first is to give full responsibility and authority to the government or local community. Second, integrate management between the government and the community. Keban lewa lolon on Solor Island offers an integrative model of sustainable coastal and marine management based on local wisdom that is known and accepted by the local community. Keban lewa lolon is a new practice on Solor Island for the protection, utilization of the coast and sea inspired by the food barn on land. The keban model integrates local wisdom with government zoning policies. From a public policy perspective, this study contributes to the design of participatory policies for the management of coastal and marine spaces based on local wisdom.